Die ‘vergroening’ van die Christelike godsdiens: Charles Darwin, Pierre Teilhard de Chardin en Lloyd Geering - Izak J.J. (Sakkie) Spangenberg (HTS Teologiese Studies/Theological Studies, 2014)
The greening of Christianity: Charles Darwin, Pierre Teilhard de Chardin and Lloyd Geering. Since the time of Charles Darwin, evolutionary biology challenged the metanarrative of Christianity which can be summarised as Fall-Redemption-Judgement. Pierre Teilhard de Chardin tried to circumvent these challenges by integrating the traditional Christian doctrines with evolutionary biology. However, he did not succeed since the Catholic Church, time and again, vetoed his theological publications. A number of Protestant theologians promoted his views but even they could not convince ordinary Christians to accept his views. These were too esoteric for Christians. Most of them were convinced that the acceptance of the theory of evolution will eventually undermine their faith. In recent years Lloyd Geering argued a case for the creation of a new narrative in which the Big Bang and the theory of evolution do play a role. He calls it the ‘Greening of Christianity’. This article discusses the metanarrative of Christianity and the challenges the theory of evolution presents before it assesses the views of Pierre Teilhard de Chardin and Lloyd Geering.